Exploring Cognitive Engagement Modes of AI Use in Language Classroom: استكشاف أنماط التفاعل المعرفي لاستخدام الذكاء الاصطناعي في تعليم اللغة - KHALDOUN , Abdelkader; BOUDCHICHE , Nawal (Maalim, 2026)
The study investigates the potential risks of deteriorating learning processes due to the systematic and excessive use of AI assistants as a medium for problem-solving in foreign language classes. In the context of a writing workshop inviting 15 second year Master's students of English and 10 students of the same level enrolled in French didactics to engage in writing activities, through non-participant observation combined with structured interviews, indicators of work situations unfavourable to active learning. The combined theoretical frameworks of active learning and the ICAP model of cognitive engagement denote that the use of AI tools creates a pedagogical environment undesirable to the development of students’ knowledge and skills. The obtained results instruct foreign language educators towards the necessity of training students using digital didactic culture.